DYNAMICS OF AIRBORNE MICROPLASTICS (AMPS) IN BANDUNG CITY: CONCENTRATION, CHEMICAL COMPOSITION, SIZE, SHAPE, AND DEGRADATION LEVEL - Felita Shandy, Aurellia
Microplastics have attracted increasing attention due to their presence in various environments. While most research focuses on microplastics in the aquatic habitat, there is still a lack of understanding of airborne microplastics (AMPs). This study addresses the gap by investigating AMPs dynamics in an urban area. Concentration and characteristics of AMPs in Bandung City were examined over four periods between December 2022 and March 2023 using ?-FTIR analysis and ATR imaging. Additionally, the degradation level of AMPs was assessed via the Carbonyl Index from IR spectra data. AMPs concentration averaged 6.63 ± 5.76 particles/m³. Seven types of polymers were identified: polyethylene (PE, 98.06%), ethylene-vinyl acetate (EVA, 0.22%), polyethylene terephthalate (PET, 1.08%), poly diallyl phthalate (PDAP, 0.32%), polybutadiene rubber (PBR, 0.11%), polyvinyl alcohol (PVA, 0.11%), and polycaprolactone (PCL, 0.11%). Maximum feret diameter of AMPs ranged from 3.14 – 512 ?m, averaging 21.37 ± 25.91 ?m. AMPs are fragment-shaped (76.5%), granule (9.1%), fiber (9.4%), and unknown-shaped (5.0%). The average carbonyl index of PE was 0.34 ± 0.49 (point method) and 1.00 ± 0.75 (SAUB method). Most of the PE exhibited low levels of surface oxidation (45%) compared to high (33%) and medium levels (22%). It is estimated that 31% of PE from sample S1 and 10% of PE from sample S2 have an age of less than 30 days. AMPs are mainly derived from larger plastic fragmentation, textile shedding, and road dust. AMPs can originate from local sources or long-distance transport from the south and west of the sampling site. The findings of this study advance the understanding of atmospheric microplastics and provide a basis for developing mitigation strategies to address this environmental problem.